Preclinical evidence for supra-clinical acute kidney injury: current biomarkers are not enough - Justine Serre; David Legouis; Sandrine Placier; Charles Verney; Wionna Desvarieux; David Buob; Pierre Galichon; Juliette Hadchouel (Intensive Care Medicine Experimental, 2026)
Abstract Background Acute kidney injury (AKI) is a frequent complication in hospitalized patients, affecting up to 50% of those in intensive care units (ICU). It is linked to high morbidity and mortality, with severity closely tied to patient outcomes. While early biomarkers like KIM1 and NGAL can detect subclinical AKI, their practical benefit is limited, as treatment must begin at suspicion rather than biomarker confirmation. Conversely, when injury exceeds serum creatinine’s diagnostic capacity, a “blind spot” emerges, highlighting the need for “supra-clinical” AKI biomarkers. The KDIGO staging system, based on urine output and creatinine, lacks granularity: even in stage 3, outcomes range from full recovery to permanent dialysis. Anuric patients, despite complete loss of filtration, also show heterogeneous recovery, suggesting injury severity influences prognosis. This study aims to explore “supra-clinical” AKI and assess whether further injury occurs beyond current clinical markers using a preclinical ischemia-reperfusion model and human single-cell transcriptomic data. Results We performed unilateral renal ischemia of increased duration (5-30 minutes), associated with contralateral nephrectomy, in mice. Plasma urea and creatinine concentration reached a plateau when ischemia duration exceeded 10 minutes. In contrast, we observed a continuous increase in the severity of the renal lesions with the ischemia duration. Similarly, the expression level of Quinolinate phosphoribosyltransferase (QPRT), an enzyme contributing to the biosynthesis of nicotinamide adenine dinucleotide (NAD), was inversely correlated to the ischemia duration. Using single-nucleus RNA sequencing data on human kidney biopsies from ICU patients, we showed a largely reciprocal distribution of QPRT and KIM1 (Kidney Injury Marker 1), expressed specifically in injured proximal tubule cells. Conclusions Our data demonstrate the existence of a “supra-clinical” stage in AKI, where more ischemia causes more histological and metabolic injury than serum creatinine, serum urea and KIM1 expression can reflect. This highlights a critical diagnostic blind spot: there are currently no available biomarkers to distinguish several stages of AKI when the plasma creatinine concentration does not increase further, or in patients treated with dialysis.